Bisphenol A type transparent porous hydrogel and preparation method thereof

By copolymerizing bisphenol A diglycidyl ether and polyethylene glycol glycidyl ether, a micro-phase-separated transparent porous hydrogel is prepared by using thermodynamic incompatibility, which solves the problems of uneven and opaque pore sizes of existing materials, and achieves a hydrogel with high transparency and good mechanical properties.

CN119875062AActive Publication Date: 2025-04-25DALIAN UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510125821.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-27
Publication Date
2025-04-25
Estimated Expiration
2045-01-27

AI Technical Summary

Technical Problem

Existing porous hydrogel preparation methods lead to materials having large pore sizes or uneven pore distributions and often in opaque states, limiting their application.

Method used

Microphase-separated transparent porous hydrogels were prepared by copolymerizing bisphenol A diglycidyl ether with polyethylene glycol glycidyl ether, and using the thermodynamic incompatibility between the rigid and flexible segments.

Benefits of technology

High transparency and good mechanical properties were achieved, the pore size is in the range of 122-330nm, and the transparency reaches 83.2-96.3%, while alleviating the supply pressure of the bisphenol A market.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875062A_ABST
    Figure CN119875062A_ABST
Patent Text Reader

Abstract

The invention provides bisphenol A type transparent porous hydrogel and a preparation method thereof, and belongs to the technical field of high polymer material preparation. The transparent porous hydrogel is prepared by the following steps: polymerizing bisphenol A diglycidyl ether, polyethylene glycol glycidyl ether and an amino monomer into a polyhydroxy prepolymer based on a simple and efficient amino-epoxy click reaction, further adding an isocyanate chemical cross-linking agent, and reacting with hydroxyl to form a cross-linked polymer network; and then immersing the cross-linked polymer network into water. The pores are generated based on thermodynamically incompatible microphase separation between a bisphenol A chain segment and a polyethylene glycol chain segment after copolymerization. The invention provides a brand-new and universal method for preparing the porous hydrogel by a phase separation method, the prepared hydrogel has good transparency, bisphenol A diglycidyl ether is innovatively applied to the field of hydrogel, and an effective way is provided for relieving the pressure of the bisphenol A market in China.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer material preparation, and relates to a bisphenol A type transparent porous hydrogel and a preparation method thereof. Background Art

[0002] In recent years, the domestic bisphenol A market has entered a new stage of development. The further expansion of domestic supply and the mismatch with market demand have led to a continuous decline in product prices and increased industry losses. Bisphenol A diglycidyl ether is not only the main downstream product of bisphenol A, but also the most commonly used epoxy resin in industry. Its preparation process is mature and the price is low. It is favored by researchers and is often used in coatings, adhesives, molding materials and other fields. Faced with the current situation of oversupply of domestic products, finding new application areas can undoubtedly alleviate the market pressure of my country's bisphenol A market. As an important soft material, hydrogel has received more and more attention in the fields of flexible electronic devices, pollution control and biomedicine. The application of bisphenol A diglycidyl ether in the field of hydrogel not only broadens the preparation method of hydrogel, but also alleviates the market supply pressure of bisphenol A, which has great research value.

[0003] Compared with ordinary hydrogels, porous hydrogels have stronger water absorption capacity, can quickly absorb water through capillary action, increase the contact area between hydrophilic groups and water molecules, and show great potential in various applications. Common methods for porous hydrogels include template method, foaming method, phase separation method, etc. Template method refers to the method of using template substances to form voids in hydrogels, and then removing the template substances to form a porous structure. However, porous materials prepared by the template method generally have poor mechanical properties and a single pore size. Due to the sacrifice of template materials, it is difficult to prepare on a large scale. The foaming method uses chemical substances to decompose at high temperature to produce gas to form bubbles during the polymerization process. After the bubbles expand, they leave holes in the polymer to obtain porous structure polymers. In addition to generating bubbles through chemical reactions, mechanical stirring can also be used to generate bubbles to prepare porous hydrogels. However, porous materials prepared by chemical foaming or mechanical stirring usually have a wide pore size distribution, ranging from a few microns to hundreds of microns. Compared with other methods, the phase separation method has obvious advantages such as simplicity, easy operation and low cost. The porous polymer network prepared by this method is mostly connected by covalent bonds and has high mechanical properties. However, the phase separation method is often limited by the type of polymerization monomer and the special properties of the polymer and cannot be widely used. The hydrogels prepared by these common porous hydrogel preparation methods have larger pore sizes or uneven pore distributions, and are mostly opaque, which limits the application of hydrogels to a certain extent. Therefore, it is very necessary to develop a new method to achieve the consumption of bisphenol A diglycidyl ether and the transparency of porous hydrogels. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a type of bisphenol A type transparent porous hydrogel and a preparation method thereof. The present invention copolymerizes bisphenol A diglycidyl ether with polyethylene glycol glycidyl ether, and utilizes the thermodynamic incompatibility between the rigid segments generated by bisphenol A diglycidyl ether and the flexible segments generated by polyethylene glycol glycidyl ether after copolymerization to prepare a microphase separation hydrogel. By adjusting the ratio and dosage between various raw materials, the pores are controlled and high transparency is achieved. The purpose of the present invention is to prepare a new type of highly transparent hydrogel and thereby realize the consumption of bisphenol A products, which is conducive to alleviating the market pressure of bisphenol A.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] A type of bisphenol A type transparent porous hydrogel, the transparent porous hydrogel is based on a simple and efficient "amino-epoxy" click reaction, bisphenol A diglycidyl ether and polyethylene glycol glycidyl ether with different feed ratios are polymerized with different amino monomers to form a polyhydroxy prepolymer, and isocyanate chemical crosslinking agents with different feed ratios and structures are further added to react with hydroxyl groups to form a crosslinked polymer network, and then the crosslinked polymer network is immersed in water to prepare. After the rigid bisphenol A chain segment and the flexible polyethylene glycol chain segment are copolymerized, a microphase separation porous structure is generated due to thermodynamic incompatibility, which is conducive to the water absorption process of the hydrogel.

[0007] The structural formula of the bisphenol A diglycidyl ether is as follows:

[0008]

[0009] The structural formula of the polyethylene glycol glycidyl ether (Mn=500-6000g / mol) is as follows:

[0010]

[0011] The amino monomers include 3-amino-1-propanol, 6-amino-1-hexanol, 2-amino-1-butanol, N,N'-dimethylhexanediamine, and N,N'-dimethyl-1,3-propylenediamine, and the structural formulas are as follows:

[0012]

[0013] Furthermore, the chemical crosslinking agent includes hexamethylene diisocyanate (HDI), diphenylmethane diisocyanate (MDI), and dicyclohexylmethane diisocyanate (HMDI), and the structural formulas are as follows:

[0014]

[0015] The microphase separation refers to the fact that the structural difference between the rigid segment and the flexible segment after the copolymerization of bisphenol A diglycidyl ether and polyethylene glycol glycidyl ether is large, and they cannot be evenly dispersed at the molecular level. Since it is not a completely thermodynamically stable system, phase separation occurs. This phase separation does not show macroscopic stratification in appearance, but the existence of two phases can be observed with the help of high-resolution means.

[0016] A method for preparing a bisphenol A type transparent porous hydrogel comprises the following steps:

[0017] In the first step, the polyhydroxy prepolymer PBAPEG was prepared by "amino-epoxy" click polymerization under inert gas protection.

[0018] First, bisphenol A diglycidyl ether and polyethylene glycol glycidyl ether are added to 15-30 ml of an organic solvent and fully dissolved, and then an amino monomer is added and stirred to obtain a mixed solution, and the mixture is stirred in an oil bath at 60-140° C. for 6-14 hours. After the reaction is completed, the heating is turned off and the stirring is continued to wait for the system to cool down naturally to obtain a linear prepolymer solution containing a polyhydroxy prepolymer PBAPEG.

[0019] Furthermore, the organic solvent includes N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), and tetrahydrofuran (THF).

[0020] Furthermore, the molar ratio of bisphenol A diglycidyl ether to polyethylene glycol glycidyl ether is 1:(0.25-4), wherein the concentration of bisphenol A diglycidyl ether in the mixed solution is 0.133-0.533 mol / L; the amount of the amino monomer is 0.75-0.95 times the total molar amount of bisphenol A diglycidyl ether and polyethylene glycol glycidyl ether epoxy monomer.

[0021] In the second step, a cross-linked polymer network PBAPEGPU is generated by reacting a chemical cross-linking agent with the polyhydroxy prepolymer PBAPEG.

[0022] First, add the chemical crosslinking agent to the linear prepolymer solution, stir it evenly, and transfer it to a horizontal mold in the oven; second, turn on the vacuum pump to put the oven in a negative pressure state until there are no obvious bubbles in the solution, and open the vent valve to restore the oven to atmospheric pressure. Finally, set the oven temperature to 40-70°C, and observe the polymer change from liquid to solid after 36-48 hours. Transfer it to a fume hood, and obtain an elastomeric crosslinked polymer PBAPEGPU after the solvent is completely evaporated.

[0023] Furthermore, the molar ratio of the crosslinking agent to the amino monomer is (0.3-0.75):1.

[0024] Furthermore, the stirring time is 5-15 min.

[0025] Furthermore, the chemical cross-linking agent is diluted with 2-4 ml of an organic solvent and then added dropwise to the linear prepolymer solution.

[0026] The third step is to obtain the transparent porous hydrogel WPBAPEGPU by immersion method.

[0027] The cross-linked polymer network PBAPEGPU was immersed in water for 10-30 min to obtain a transparent porous hydrogel WPBAPEGPU.

[0028] Experimental tests of the present invention:

[0029] (1) Characterization of thermal properties of cross-linked polymer network PBAPEGPU: Differential scanning calorimetry data were obtained using a TA Instruments-Q2000 differential scanning calorimeter. The test conditions were heating or cooling at a rate of 10°C / min in the temperature range of -70°C to 70°C. Before the formal test, the material was given a heat history of 10°C / min.

[0030] (2) Tensile test of the cross-linked polymer network PBAPEGPU: Instron 5567A material testing machine was used to perform tensile tests at a rate of 5 mm / min at room temperature.

[0031] (3) Characterization of the micromorphology of the cross-linked polymer network PBAPEGPU: The micromorphology was measured using a HITACHI-SU5000 field emission electron microscope.

[0032] (4) Hydrogel WPBAPEGPU water absorption swelling test and swelling rate calculation method:

[0033] The cross-linked polymer network PBAPEGPU is placed in water until the weight change reaches a stable state. The swelling ratio is calculated as shown in Formula 1: SR = (m2-m1) / m2*100% (Formula 1)

[0034] Where: SR-swelling ratio, m1 is the weight of the cross-linked polymer network PBAPEGPU before swelling due to water absorption, and m2 is the weight of the hydrogel WPBAPEGPU after swelling due to water absorption.

[0035] (5) Transparency test: The transparency of the cross-linked polymer network PBAPEGPU and the hydrogel WPBAPEGPU was tested using an RT-6000 transparency tester.

[0036] The innovative features of the present invention are:

[0037] The present invention has developed a new and universal method for preparing porous hydrogels by microphase separation. Through efficient and selective "amino-epoxy" click polymerization, substances with structural differences are copolymerized, and the thermodynamic incompatibility between the structures is used to form a microscopic porous structure of microphase separation. The prepared hydrogel has good transparency, which provides a new idea for the preparation of transparent porous hydrogels. In addition, the innovative application of bisphenol A diglycidyl ether in the field of hydrogels provides an effective way to reduce the pressure on the bisphenol A market in my country.

[0038] The beneficial effects of the present invention are:

[0039] The present invention uses thermodynamic incompatibility between rigid bisphenol A segments and flexible hydrophilic polyethylene glycol segments to produce micropores with a maximum size of 122-330 nm through microphase separation, so that the PBAPEGPU has a transparency of 83.2-87.9%, and the corresponding WPBAPEGPU has a transparency of 88.9-96.3%. Simple and efficient "amino-epoxy" click polymerization ensures the smooth progress of the reaction, and the two-step cross-linking method ensures the repeatability of material preparation. Various transparent porous hydrogels are prepared by changing the type of amino monomer, the feed ratio of each component, the type of chemical cross-linking agent, etc. The tensile strength of the obtained PBAPEGPU cross-linked polymer network is in the range of 1.01-10.48MPa, and the elongation at break is in the range of 86.3-238.1%, and has good mechanical properties. The glass transition temperature is in the range of -18°C-12°C, and it behaves as a soft elastomeric material at room temperature. The water absorption and swelling rate of the hydrogel WPBAPEGPU is in the range of 40.2-96.8%, which can achieve a high water absorption and swelling rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a scanning electron microscope photograph of the PBAPEGPU cross-linked polymer network of Example 2. DETAILED DESCRIPTION

[0041] The present invention is further described below in conjunction with specific embodiments.

[0042] Example 1

[0043] In the first step, the polyhydroxy prepolymer PBAPEG was prepared by "amino-epoxy" click polymerization under inert gas protection.

[0044] First, bisphenol A diglycidyl ether (0.002 mol, 0.68 g) and polyethylene glycol glycidyl ether (1000 g / mol, 0.008 mol, 8 g) were added to 30 ml of DMF and fully dissolved, and then 6-amino-1-hexanol (0.0075 mol, 0.88 g) was added and stirred to obtain a mixed solution, which was stirred in an oil bath at 140° C. for 14 h. After the reaction was completed, the heating was turned off and the stirring was continued to wait for the system to cool down naturally to obtain a linear prepolymer solution containing a polyhydroxy prepolymer PBAPEG.

[0045] In the second step, a chemical crosslinking agent is reacted with the polyhydroxy prepolymer PBAPEG to generate a crosslinked polymer PBAPEGPU.

[0046] First, the chemical crosslinking agent HDI (0.00225mol, 0.38g) was diluted with 2ml DMF and added to the linear prepolymer solution, stirred for 15min, and transferred to a mold placed horizontally in an oven; secondly, the vacuum pump was turned on to observe the changes in the solution in the mold, and the oven was placed in a negative pressure state until there were no obvious bubbles in the solution, and the vent valve was opened to restore the oven to atmospheric pressure. Finally, the oven temperature was set to 70℃, and after 48h, the polymer was observed to change from liquid to solid. It was transferred to a fume hood, and the DMF solvent was completely evaporated to obtain an elastomeric crosslinked polymer PBAPEGPU. Its tensile strength is 1.01MPa, the elongation at break is 238.1%, the glass transition temperature is -18℃, the maximum pore size is 330nm, and the transparency is 83.2%.

[0047] The third step is to obtain the transparent porous hydrogel WPBAPEGPU by immersion method.

[0048] The cross-linked polymer network PBAPEGPU was immersed in water for 10 min to obtain a transparent porous hydrogel WPBAPEGPU, which had a swelling ratio of 93.8% and a high transparency of 96.3%.

[0049] Example 2

[0050] In the first step, the polyhydroxy prepolymer PBAPEG was prepared by "amino-epoxy" click polymerization under inert gas protection.

[0051] First, bisphenol A diglycidyl ether (0.005 mol, 1.7 g) and polyethylene glycol glycidyl ether (Mn = 500 g / mol, 0.005 mol, 2.5 g) were added to 15 ml of DMF and fully dissolved, and then 3-amino-1-propanol (0.0085 mol, 0.64 g) was added and stirred to obtain a mixed solution, which was stirred in an oil bath at 120° C. for 12 h. After the reaction was completed, the heating was turned off and the stirring was continued to wait for the system to cool down naturally to obtain a linear prepolymer solution containing a polyhydroxy prepolymer PBAPEG.

[0052] In the second step, a chemical crosslinking agent is reacted with the polyhydroxy prepolymer PBAPEG to generate a crosslinked polymer PBAPEGPU.

[0053] First, the chemical crosslinking agent HDI (0.003825mol, 0.64g) was diluted with 2.5ml DMF and added to the linear prepolymer solution, stirred for 10min, and transferred to a mold placed horizontally in an oven; secondly, the vacuum pump was turned on to observe the changes in the solution in the mold, and the oven was placed in a negative pressure state until there were no obvious bubbles in the solution, and the vent valve was opened to restore the oven to atmospheric pressure. Finally, the oven temperature was set to 70℃, and after 48h, the polymer was observed to change from liquid to solid. It was transferred to a fume hood, and the DMF solvent was completely evaporated to obtain an elastomeric crosslinked polymer PBAPEGPU. Its tensile strength is 2.26MPa, the elongation at break is 171.0%, the glass transition temperature is -4℃, the maximum pore size is 122nm, and the transparency is 87.9%.

[0054] The third step is to obtain the transparent porous hydrogel WPBAPEGPU by immersion method.

[0055] The cross-linked polymer network PBAPEGPU was immersed in water for 15 min to obtain a transparent porous hydrogel WPBAPEGPU, which had a swelling ratio of 69.7% and a high transparency of 94.3%.

[0056] Depend on Figure 1 Scanning electron microscope photos show that the pores of the PBAPEGPU cross-linked polymer network are as small as nanometer size.

[0057] Example 3

[0058] In the first step, the polyhydroxy prepolymer PBAPEG was prepared by "amino-epoxy" click polymerization under inert gas protection.

[0059] First, bisphenol A diglycidyl ether (0.007 mol, 2.38 g) and polyethylene glycol glycidyl ether (6000 g / mol, 0.003 mol, 18 g) were added to 25 ml THF and fully dissolved, and then N, N'-dimethylhexanediamine (0.008 mol, 0.71 g) was added and stirred to obtain a mixed solution, which was stirred in an oil bath at 65°C for 8 h. After the reaction was completed, the heating was turned off and the stirring was continued to wait for the system to cool down naturally to obtain a linear prepolymer solution containing a polyhydroxy prepolymer PBAPEG.

[0060] In the second step, a chemical crosslinking agent is reacted with the polyhydroxy prepolymer PBAPEG to generate a crosslinked polymer PBAPEGPU.

[0061] First, the chemical crosslinking agent HMDI (0.0036mol, 0.94g) was diluted with 3ml DMF and added to the linear prepolymer solution, stirred for 12min, and transferred to a mold placed horizontally in an oven; secondly, the vacuum pump was turned on to observe the changes in the solution in the mold, and the oven was placed in a negative pressure state until there were no obvious bubbles in the solution, and the vent valve was opened to restore the oven to atmospheric pressure. Finally, the oven temperature was set to 50℃, and after 38h, the polymer was observed to change from liquid to solid. It was transferred to a fume hood, and the elastomeric crosslinked polymer PBAPEGPU was obtained after the THF solvent was completely evaporated. Its tensile strength is 1.12MPa, the elongation at break is 186.3%, the glass transition temperature is -16℃, the maximum pore size is 188nm, and the transparency is 86.4%.

[0062] The third step is to obtain the transparent porous hydrogel WPBAPEGPU by immersion method.

[0063] The cross-linked polymer network PBAPEGPU was immersed in water for 15 minutes to obtain a transparent porous hydrogel WPBAPEGPU, with a swelling ratio of 96.8% and a transparency of 96.2%.

[0064] Example 4

[0065] In the first step, the polyhydroxy prepolymer PBAPEG was prepared by "amino-epoxy" click polymerization under inert gas protection.

[0066] First, bisphenol A diglycidyl ether (0.004 mol, 1.36 g) and polyethylene glycol glycidyl ether (0.006 mol, 3 g) were added to 30 ml THF and fully dissolved, and then N, N'-dimethyl-1,3-propylenediamine (0.009 mol, 0.92 g) was added and stirred to obtain a mixed solution, which was stirred in an oil bath at 60°C for 10 h. After the reaction was completed, the heating was turned off and the stirring was continued to wait for the system to cool down naturally to obtain a linear prepolymer solution containing a polyhydroxy prepolymer PBAPEG.

[0067] In the second step, a chemical crosslinking agent is reacted with the polyhydroxy prepolymer PBAPEG to generate a crosslinked polymer PBAPEGPU.

[0068] First, the chemical crosslinking agent MDI (0.0054 mol, 1.35 g) was diluted with 3.5 ml DMF and added to the linear prepolymer solution, stirred for 15 min, and transferred to a mold placed horizontally in an oven; secondly, the vacuum pump was turned on to observe the changes in the solution in the mold, and the oven was placed in a negative pressure state until there were no obvious bubbles in the solution, and the vent valve was opened to restore the oven to atmospheric pressure. Finally, the oven temperature was set to 40 ° C. After 44 hours, the polymer was observed to change from liquid to solid. It was transferred to a fume hood, and the elastomeric crosslinked polymer PBAPEGPU was obtained after the THF solvent was completely evaporated. Its tensile strength is 3.45 MPa, the elongation at break is 163.1%, the glass transition temperature is 1 ° C, the maximum pore size is 153 nm, and the transparency is 87.1%.

[0069] The third step is to obtain the transparent porous hydrogel WPBAPEGPU by immersion method.

[0070] The cross-linked polymer network PBAPEGPU was immersed in water for 25 minutes to obtain a transparent porous hydrogel WPBAPEGPU, with a swelling ratio of 61.0% and a transparency of 92.0%.

[0071] Example 5

[0072] In the first step, the polyhydroxy prepolymer PBAPEG was prepared by "amino-epoxy" click polymerization under inert gas protection.

[0073] First, bisphenol A diglycidyl ether (0.008 mol, 2.72 g) and polyethylene glycol glycidyl ether (500 g / mol, 0.002 mol, 1 g) were added to 15 ml of DMSO and fully dissolved, and then 2-amino-1-butanol (0.0095 mol, 0.85 g) was added and stirred to obtain a mixed solution, which was stirred in an oil bath at 60° C. for 6 h. After the reaction was completed, the heating was turned off and the stirring was continued to wait for the system to cool down naturally to obtain a linear prepolymer solution containing a polyhydroxy prepolymer PBAPEG.

[0074] In the second step, a chemical crosslinking agent is reacted with the polyhydroxy prepolymer PBAPEG to generate a crosslinked polymer PBAPEGPU.

[0075] First, the chemical crosslinking agent MDI (0.007125mol, 1.78g) was diluted with 4ml DMF and added to the linear prepolymer solution, stirred for 5min, and transferred to a mold placed horizontally in an oven; secondly, the vacuum pump was turned on to observe the changes in the solution in the mold, and the oven was placed in a negative pressure state until there were no obvious bubbles in the solution, and the vent valve was opened to restore the oven to atmospheric pressure. Finally, the oven temperature was set to 40℃, and after 36h, the polymer was observed to change from liquid to solid. It was transferred to a fume hood, and the DMSO solvent was completely evaporated to obtain an elastomeric crosslinked polymer PBAPEGPU. Its tensile strength is 10.48MPa, the elongation at break is 86.3%, the glass transition temperature is 12℃, the maximum pore size is 283nm, and the transparency is 84.3%.

[0076] The third step is to obtain the transparent porous hydrogel WPBAPEGPU by immersion method.

[0077] The cross-linked polymer network PBAPEGPU was immersed in water for 30 minutes to obtain a transparent porous hydrogel WPBAPEGPU, with a swelling ratio of 40.2% and a transparency of 88.9%.

[0078] The above-described embodiments merely express the implementation methods of the present invention, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing a bisphenol A type transparent porous hydrogel, characterized in that: The preparation method is based on an "amino-epoxy" click reaction, wherein bisphenol A diglycidyl ether and polyethylene glycol glycidyl ether in different feed ratios are polymerized with different amino monomers to form a polyhydroxy prepolymer, and then isocyanate chemical crosslinking agents in different feed ratios and structures are added to react with hydroxyl groups to form a crosslinked polymer network, and finally the crosslinked polymer network is immersed in water to prepare the method.

2. The method for preparing a bisphenol A type transparent porous hydrogel according to claim 1, characterized in that: The following steps are involved: The first step is to prepare the polyhydroxy prepolymer PBAPEG by "amino-epoxy" click polymerization under the protection of inert gas; First, bisphenol A diglycidyl ether and polyethylene glycol glycidyl ether are added to an organic solvent and fully dissolved, and then an amino monomer is added and stirred to obtain a mixed solution, and the solution is stirred in an oil bath at 60-140° C. for 6-14 hours; after the reaction is completed, the solution is cooled naturally to obtain a linear prepolymer solution containing a polyhydroxy prepolymer PBAPEG; In the second step, a cross-linked polymer network PBAPEGPU is generated by reacting a chemical cross-linking agent with the polyhydroxy prepolymer PBAPEG; First, a chemical cross-linking agent is added to the linear prepolymer solution, stirred evenly, and transferred to a horizontally placed mold in an oven; Secondly, the vacuum pump was turned on to keep the oven in a negative pressure state until there were no obvious bubbles in the solution, and the vent valve was opened to restore the oven to atmospheric pressure; finally, the oven temperature was set to 40-70°C, and after 36-48 hours, the polymer was observed to change from liquid to solid, and it was transferred to a fume hood, and the elastomeric cross-linked polymer PBAPEGPU was obtained after the solvent was completely evaporated; The third step is to obtain the transparent porous hydrogel WPBAPEGPU by immersion method.

3. The method for preparing a bisphenol A type transparent porous hydrogel according to claim 2, characterized in that: The molar ratio of bisphenol A diglycidyl ether to polyethylene glycol glycidyl ether is 1:(0.25-4), wherein the concentration of bisphenol A diglycidyl ether in the mixed solution is 0.133-0.533 mol / L; the amount of the amino monomer is 0.75-0.95 times the total molar amount of the bisphenol A diglycidyl ether and polyethylene glycol glycidyl ether epoxy monomer.

4. The method for preparing a bisphenol A type transparent porous hydrogel according to claim 2, characterized in that: The molar ratio of the crosslinking agent to the amino monomer is (0.3-0.75):

1.

5. The method for preparing a bisphenol A type transparent porous hydrogel according to claim 2, characterized in that: The amino monomers include 3-amino-1-propanol, 6-amino-1-hexanol, 2-amino-1-butanol, N,N'-dimethylhexanediamine or N,N'-dimethyl-1,3-propylenediamine; the chemical crosslinking agents include hexamethylene diisocyanate, diphenylmethane diisocyanate, and dicyclohexylmethane diisocyanate.

6. The method for preparing a bisphenol A type transparent porous hydrogel according to claim 2, characterized in that: The organic solvent includes N,N-dimethylformamide, dimethyl sulfoxide and tetrahydrofuran.

7. The method for preparing a bisphenol A type transparent porous hydrogel according to claim 2, characterized in that: In the third step, the chemical crosslinking agent is diluted with 2-4 ml of an organic solvent and then added dropwise to the linear prepolymer solution.

8. The method for preparing a bisphenol A type transparent porous hydrogel according to claim 2, characterized in that: In the third step, the stirring time is 5-15 min.

9. The method for preparing a bisphenol A type transparent porous hydrogel according to claim 2, characterized in that: In the fourth step, the cross-linked polymer network PBAPEGPU is immersed in water for 10-30 minutes to obtain a transparent porous hydrogel WPBAPEGPU.

10. A bisphenol A type transparent porous hydrogel, characterized in that: The bisphenol A type transparent porous hydrogel is prepared by the preparation method described in any one of claims 1-9.

Citation Information

Patent Citations

  • Selective membrane having a high fouling resistance and preparation method thereof

    EP2140929A1

  • Wood-treatment method comprising in situ polymerization under electromagnetic radiation

    US20070122558A1

  • Super Elastic Epoxy Hydrogel

    US20090317442A1

  • Thermoformable ophthalmic lens

    WO2001005578A1